Vegetation types shape the soil micro-food web compositions and soil multifunctionality in Loess Plateau - Chen, Zhiming; Kang, Wenjuan; He, Renyuan; Li, Guang; Luo, Zhuzhu (Frontiers in Microbiology, 2025)
IntroductionVegetation degradation and soil erosion are severe problems in the Loess hilly region, rendering it one of the most ecologically vulnerable areas in China and globally. Vegetation restoration has been recognized as an effective approach to amending the fragile ecological environment and restoring degraded ecosystems.MethodsThe effects of different vegetation types: Caragana korshinskii, Prunus armeniaca L., Pinus tabuliformis Carrière, Medicago sativa L., and the control vegetation Stipa bungeana on soil micro-food webs and soil multifunctionality, as well as their response mechanisms to soil environmental drivers, were investigated using High-throughput sequencing technology.ResultsC. korshinskii significantly enhanced soil physicochemical properties and soil enzyme activities by facilitating the stability of the soil micro-food web structure driven by soil bacteria and fungi and increasing the soil multifunctionality in contrast to S. bungeana. Prunus armeniaca also improved soil multifunctionality by promoting soil organic carbon and alkaline phosphatase activity. However, the stability of the soil micro-food web structure and soil multifunctionality were suboptimal in P. tabuliformis and M. sativa. Soil pH, along with carbon, nitrogen, and phosphorus cycling nutrients and enzymes, profoundly influences the structure of the soil micro-food web and soil multifunctionality; among these factors, those related to the carbon and phosphorus cycles are identified as key influencing factors.DiscussionTherefore, a vegetation restoration strategy prioritizing C. korshinskii as the dominant vegetation type, supplemented by P. armeniaca, significantly impacts restoring soil multifunctionality and stabilizing the soil micro-food web in Loess hill regions and comparable ecological areas.